Potential Drug-drug Interactions Analysis in Children Out-patients with Bronchopneumonia Medication Prescriptions - Ilil Maidatuz Zulfa; Fitria Dewi Yunitasari; Susanty Kartika Dewi (Borneo Journal of Pharmacy, 2020)
Drug-drug interactions (DDIs) is defined as the alteration of efficacy and toxicity of some drugs in the presence of other drugs. In the treatments of bronchopneumonia in outpatient settings, there is a lack of documentation of DDIs. This study was aimed to observe the potential DDIs on the prescriptions of children with bronchopneumonia. An observational and cross-sectional study was conducted on outpatient children with bronchopneumonia prescriptions during 2017. Potential for DDI was identified by online drug interaction checkers. The potential DDI then classified based on its severity (minor, moderate, and major) and mechanism (pharmacokinetic and pharmacodynamic). Among 86 prescriptions analyzed, potential DDIs observed at 48.84% of it. Of that, there were 67 potential DDIs where 72.34% of it were categorized as moderate. The majority of potential DDIs was pharmacodynamic interaction (76.12%) with the most frequently involved drug pair was Ephedrine-Salbutamol (29.85%). Children outpatients with bronchopneumonia are at risk of potential DDIs, especially to minor and moderate potential DDIs. Prescriptions screening for potential DDIs followed by monitoring of therapeutical effects and associated adverse drug events will optimize patient safety.